HUBUNGAN PERSEPSI TENTANG MANAJEMEN PELAYANAN PIK-KRR DENGAN KEPUASAN PENGUNJUNG PADA SISWA SMA X SEMARANG TRIWULAN II TAHUN 2017 - Herpina Simarmata; Farid Agusyahbana; Atik Mawarni; Djoko Nugroho (Jurnal Kesehatan Masyarakat (Undip), 2017)
The results of KOMNAS PAI's latest study in 2010 on 4,500 junior and senior high school students in 12 major cities in Indonesia obtained the result of kissing, oral sex or petting (93.7%), not virgin (62.7%) and had done abortion (21.2%). Special programs focusing on adolescent reproductive health in order to ensure the fulfillment of sexual and reproductive health rights in order to provide reproductive health information as early as possible in adolescents is through the Center for Information and Counseling of Adolescent Reproductive Health (PIK-KRR). PIK-KRR located in SMA Negeri 3 Semarang is one of PIK-KRR that has been formed and actively run its activities in Semarang city since 2014. The purpose of research to analyze the relationship of perception about service management of PIK-KRR with satisfaction of visitor at SMA Negeri 3 Semarang student in 2017. This research uses explanatory research type of research with cross sectional study approach. The sample of this study uses a total population of 27 people. The result of univariate analysis shows that the perception variable about PIK-KRR service management is still poor on the implementation and supervision indicators. Variables of visitor satisfaction on aspects of tangiable, reliability, assurance and emphaty are still less satisfactory. Rank Spearman correlation statistic test shows p value 0.0001 means there is a perception relation about PIK-KRR service management with visitor satisfaction. In this study, respondent age variable is not confounding variable (counfounding), with Rank Spearman correlation test showed that age is not related to perception about service management of PIK-KRR (pvalue 0,334) and with visitor satisfaction (pvalue 0,636). Result of analysis of influence test indicate that perception about service management of PIK-KRR have an effect on visitor satisfaction with R Square value 0,585. Advice for the school as a provider of services PIK-KRR are Improved service management of PIK-KRR by way of counseling for officers to provide important information in according to the guideline of PIK-KRR management from BKKBN and Providing training to PIK-KRR officers aimed at improving communication skills in providing information on adolescent reproductive health as well as in counseling.